2022
DOI: 10.1212/wnl.0000000000201038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Biomarkers of Inflammation With Penumbra Consumption After Mechanical Thrombectomy in Patients With Acute Ischemic Stroke

Abstract: Objectives:To assess the relationship between blood biomarkers of inflammation and lesion growth within the penumbra in acute ischemic stroke (AIS) patients treated with mechanical thrombectomy (MT).Methods:HIBISCUS-STROKE cohort enrolled patients admitted in the Lyon Stroke Center for an anterior circulation AIS treated with MT following MRI. Lesion growth within the penumbra was assessed on day-6 MRI using a voxel-based nonlinear coregistration method and dichotomized into low and high according to the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
(89 reference statements)
0
9
0
Order By: Relevance
“… 10 , 30 Third, CPR is a well-established inflammatory biomarker and is related to the ischemia-reperfusion injury, post-stroke infection, and inflammatory stimuli. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“… 10 , 30 Third, CPR is a well-established inflammatory biomarker and is related to the ischemia-reperfusion injury, post-stroke infection, and inflammatory stimuli. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more studies have found that ACI can trigger the release of inflammatory factors and induce the occurrence of inflammatory responses. 19 , 20 Inflammatory reaction runs through the whole pathological process after the occurrence of ACI. 21 The higher risk of infection after ACI is associated with the suppression of immune function caused by cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…sST2 acts as a decoy receptor of IL-33 and therefore inhibits the M2 polarization effect of IL-33/ST2 signaling on microglial cells and macrophages ( 28 ). sST2 is associated with an expansion of the lesion within penumbra in AIS patients treated with MT and also with functional outcome and death ( 19 , 29 , 30 ). sST2 levels, which have proven their positive correlation with the left ventricular diameter and ejection fraction, and their diagnostic and prognostic value in heart failure, are also higher in patients with AF and are correlated with the left atrial diameter ( 15 , 31 ).…”
Section: Discussionmentioning
confidence: 99%